2012
DOI: 10.29333/ejgm/82544
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Esophageal Bronchogenic Cyst: Mimicking Malignity and Support of PET-CT in The Diagnosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A barium swallow test usually reveals a dilated hypertrophic esophagus or may show a smooth, polypoid, intraluminal space-occupying lesion and filling defects. CT of the chest shows low-density absorption of the mass, which is characteristic of adipose tissue [ 1 , 2 , 3 , 4 , 5 , 6 ]. On positron emission tomography, lower uptake values are useful for distinguishing lipomas from other malignant lesions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A barium swallow test usually reveals a dilated hypertrophic esophagus or may show a smooth, polypoid, intraluminal space-occupying lesion and filling defects. CT of the chest shows low-density absorption of the mass, which is characteristic of adipose tissue [ 1 , 2 , 3 , 4 , 5 , 6 ]. On positron emission tomography, lower uptake values are useful for distinguishing lipomas from other malignant lesions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal diverticula are also uncommon benign pathologies, which can be located at any level of the esophagus, but the most common localization is the cervical part of the esophagus where they present as pulsion diverticula. They are classified either as traction or pulsion diverticula, and the primary treatment strategy is diverticulectomy [ 6 ]. To the best of our knowledge, esophageal diverticula requiring surgical manipulation after the resection of benign esophageal tumors have not been described before.…”
Section: Introductionmentioning
confidence: 99%
“…According to Maier, localization of these cysts can be: paratracheal, carinal, paraesophageal and hilar, and they can be connected with the tracheobronchial airways [1,7]. Intramural esophageal bronchogenic cyst which has a very rare localization [8] and intrapericardial bronchogenic cyst have been described in literature. Ectopic extrathoracic localization of bronchogenic cyst involves cervical, abdominal and subcutaneous cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported a case of retroperitoneal uncomplicated bronchogenic cysts with no FDG uptake on 18 F-FDG PET/CT scans [7]. Yekeler et al also reported a case of an intramural esophageal bronchogenic cyst without FDG uptake on an 18 F-FDG PET/ CT scan [8]. This case also showed a paraadrenal tumor without definite FDG uptake in the left paraadrenal area.…”
Section: Discussionmentioning
confidence: 99%